Atrial and Sinoatrial Node Development in the Zebrafish Heart - Kendall E. Martin; Joshua S. Waxman (Journal of Cardiovascular Development and Disease, 2021)
Proper development and function of the vertebrate heart is vital for embryonic and postnatal life. Many congenital heart defects in humans are associated with disruption of genes that direct the formation or maintenance of atrial and pacemaker cardiomyocytes at the venous pole of the heart. Zebrafish are an outstanding model for studying vertebrate cardiogenesis, due to the conservation of molecular mechanisms underlying early heart development, external development, and ease of genetic manipulation. Here, we discuss early developmental mechanisms that instruct appropriate formation of the venous pole in zebrafish embryos. We primarily focus on signals that determine atrial chamber size and the specialized pacemaker cells of the sinoatrial node through directing proper specification and differentiation, as well as contemporary insights into the plasticity and maintenance of cardiomyocyte identity in embryonic zebrafish hearts. Finally, we integrate how these insights into zebrafish cardiogenesis can serve as models for human atrial defects and arrhythmias.